Routinizing Lexical Phrases on Spoken Discourse - Osman, Nazira; Jusoff, Kamaruzaman (2009)
This paper examines the effectiveness of routinizing lexical phrases to a group of second language learners. A group of proficiency class students were drilled or routinized with semi-fixed and fixed phrases which are commonly used in problem-solving group discussion. Basic frequency counts and interview were carried out to see improvement in learners’ communicative ability and how the lexical phrases benefit them. The learners can use a number of phrases appropriately in several group discussions. Thus, the practice of routinizing lexical phrases which is based on the lexical approach can be applied in second language learning.